A Comparative Study between Traditional Learning and E-Learning - Singh, Ashutosh Kumar; Yusoff, Mohd Amaluddin; Oo, Naing (CSM, Sarawak, 2009)
This paper presents a comparative study between Traditional and E-learning. Traditional learning involves a physical place where students and teacher can interact whereas E-learning is pursued in an e-space where a server and internet browsing interface is to be there. Due to a constant trend of growing student numbers across the world traditional learning will be expensive. The reason behind is the physical engagement of a teacher in this method which involves payment to the teacher for his service and other required support assets. E-learning can be a method which can ensure reduced cost while enhancing the outcome in the learning system. It is based on wireless communication networks which are widely and rapidly used due to the flexibility, freedom to use that it promotes an effective learning system. The wireless communication allows learner to receive the learning materials and lectures from anywhere as long as they are connected to the internet. Classroom education may not always succeed for online learning, when the instructor is not around which need to stimulate motivation and continual learning progress. In this paper we also discuss the merits and demerits of both the methods with the help of statistical data analysis.